ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI USAHATANI SAWI DI DESA ALIMEBUNG KECAMATAN ALOR TENGAH UTARA KABUPATEN ALOR - Emirensiana Latuan; Andri P Timung; Gersun Bubungki (JURNAL AGRIBISAINS, 2022)
In general, the farming production process runs with the requirements needed by plants, these requirements consist of land, labor, and production facilities. Data collection techniques in this study were observation, interviews, questionnaires and recording. Purposive Village Determination in Alimebung Village, Alor Tengah Utara District, Regency is one of the villages that produce mustard greens. Determination of the sample is done by using a saturated sample with a sample of 55 people. Factor analysis using t test and F test. The results of the analysis show that: Variable area of ​​land has a positive and significant effect on production, variable labor has a positive and not significant effect on production, variable capital has a positive and significant effect on production, variable management management positive and insignificant effect on production.